Harmony in Citizenship Education in Building Peaceful Schools for Students' Social Welfare - Irayanti, Irma; Istianah, Anif; Sapriya, Sapriya (Departemen Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari Banjarmasin, 2023)
This article discusses the importance of citizenship education in building a peaceful and harmonious school environment for the social welfare of elementary school students amidst the challenges of global diversity and complexity. The article describes the concept of Citizenship Education in elementary schools, and its role in shaping student character, democratic values, and active participation in society. The research method uses a literature approach by exploring and analyzing the concept of harmony in Citizenship Education in the context of peaceful schools. The results and discussion found that Citizenship Education plays an important role in forming attitudes of tolerance, mutual respect, and awareness of the rights and obligations of students in elementary schools, so it needs to be ensured that it is integrated with character education in the school curriculum as an effort to overcome challenges such as religious intolerance and fundamentalism, and lack of awareness, towards the values ​​of Pancasila and the 1945 Constitution by teaching the values ​​of peace, conflict resolution skills, and respect for human rights. Schools also play an important role in creating a peaceful environment and supporting the welfare of socially active communities through environmentally based school programs, namely adiwiyata, health assistance such as brushing teeth properly and correctly, and helping to improve student welfare by providing group therapy therapeutic (TKT) in elementary school students before facing problems and obstacles to socializing in society. It is hoped that peace education in elementary schools can play a role in forming students who are harmonious, peaceful, and prosperous.